Data Sheet 1_Safety and efficacy of remimazolam versus propofol sedation in gynecological procedures: a meta-analysis of East Asian randomized trials.docx - Ou Jin (3545237) (2025)
Background and Aim Hysteroscopy necessitates appropriate sedation to ensure patient comfort and operative success. The relative safety profile of remimazolam compared to propofol in this context is unclear. This study evaluates the safety of remimazolam in comparison to propofol for sedation during hysteroscopy and other gynecological procedures. Methods We systematically searched MEDLINE (PubMed), Embase, and Scopus from inception until September 2024. We included randomized controlled trials (RCTs) that compared remimazolam and propofol for sedation in hysteroscopy procedures. The analyses were conducted using a random-effects model by PRISMA guidelines. The main outcome was the incidence of total adverse events. Secondary outcomes comprised respiratory depression, hypotension, bradycardia, emergence time, and recovery time. Results Thirteen RCTs comprising 1765 patients (remimazolam: n = 1,026; propofol: n = 739) met the inclusion criteria. The overall incidence of adverse events was significantly lower with remimazolam compared to propofol. Remimazolam was associated with lower risks of respiratory depression (OR, 0.25; 95% CI, 0.17–0.39; p  0.00001) and hypotension (OR, 0.30; 95% CI: 0.21–0.42; p  0.00001). No significant difference was observed in bradycardia (OR, 0.53; 95% CI, 0.28–1.02; p = 0.06). Recovery time [mean difference (MD), 0.18 min; 95% CI, −0.3, 0.65] and operation time (MD, 0.02 min; 95% CI, −1.0, 1.03) were almost similar for both groups. Conclusion In patients undergoing gynecological procedures, remimazolam demonstrated a superior safety profile compared to propofol, with significantly lower rates of overall adverse events, respiratory depression, and hypotension. More studies are required to confirm these results. Systematic Review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024614416